Development of reusable composite eggshell-moringa leaf catalyst for biodiesel production. (15th September 2022) - Aleman-Ramirez, J.L.; Okoye, Patrick U.; Torres-Arellano, S.; Paraguay-Delgado, F.; Mejía-López, M.; Moreira, Joel.; Sebastian, P.J.
Graphical abstract: Highlights: Eggshell-moringa leaf composite catalyst was produced for biodiesel (BD) production. The catalyst possesses high calcium (CaO) and magnesium required for BD synthesis. The composite catalyst showed high activity reaching 94.3% FAME. The catalyst can be reused nine times without severe deactivation. Abstract: A reusable heterogeneous composite catalyst was prepared from mixtures of poultry eggshells and moringa leaves for the production of biodiesel (BD). The raw materials were mixed using a micro ball mill for 4 h and then calcinated at a temperature of 800 °C for 3 h. The developed catalyst was used to promote the transesterification reaction of soybean oil and methanol to produce BD. The X-ray diffraction results revealed the presence of predominantly CaO after activation at 800 °C. Meanwhile, the individual raw materials showed the presence of alkaline metal oxides such as CaO for the eggshell residue and Ca(OH)2, MgO and CaO for the moringa leaves. The catalyst has a surface area of 5.3 m 2 g −1 and appreciably high basicity of 4.95 mmol/g, which tailored the transesterification reaction. Under the best reaction conditions of 2 wt% catalyst loading, 12:1 methanol to soybean oil molar ratio and a reaction temperature of 65 °C, 94.3% of fatty acid methyl ester (FAME) yield was achieved in 78 min. The heterogeneous catalyst can be reused for 9 consecutive cycles with a slight decrease in activity due to leaching. The biodiesel produced meets the international quality standards of ASTM D-6751 and EN 14214. In conclusion, a combination of agro-waste sources could promote stability in the reaction medium and effectively catalyze the BD production.